Mental Illness Arises Epigenetically – Like All other Diseases - Pordeus, Vitor (Journal of Psychology and Psychotherapy Research, 2015)
It is urgent to formulate a more comprehensive synthesis regarding the pathophysiology of mental diseases in light of more contemporary evidences and theories stemming from cellular, molecular biology and evolution theory. The field of epigenetics has arisen as one of the most important scientific axis to understand development, physiology and pathophysiology in all areas of medicine with special impact in psychiatry a field that has been historically dominated by today obsolete biological models and theories. In this short review I try to reflect upon the impacts these new understandings about nature may help us to approach and treat psychic diseases.